The Impact of Environmental Factors on the Genotype of African Catfish (Clarias Gariepinus): Molecular Bases and Economic Efficiency - Bakhodirovich, Muydinov Kamoliddin (American Journal of Biology and Natural Sciences, 2026)
This article was revised in IMRAD format and translated into scientific English. It examines the environmental plasticity of the genotype of African catfish (Clarias gariepinus) in flow-through culture systems, with particular attention to gene expression, epigenetic responses, and production efficiency. Based on a 16-month monitoring period, the study assesses the effects of hydrodynamic stress, temperature stability, and high-protein pelleted feeding on growth performance, survival, and farm profitability. The findings suggest that environmental signals can activate latent molecular pathways associated with myogenesis, metabolic programming, and homeostatic regulation. Under intensive conditions, specific growth rate increased from 0.8-1.0% to 1.5-2.0%, survival rose from 60-70% to 90%, and the production cycle shortened from 12 months to 6-8 months. These results indicate that the combined management of genotype, environment, and feeding strategy can significantly improve both biological productivity and economic efficiency in African catfish farming.